Low-Volume High-Intensity Interval Training as a Therapy for Type 2 Diabetes - Alvarez, C.; Ramirez-Campillo, R.; Martinez-Salazar, C.; Mancilla, R.; Flores-Opazo, M.; Cano-Montoya, J.; Ciolac, E. G. [UNESP] (Thieme, 2016)
Our purpose was to investigate the effects of low-volume, high-intensity interval training (HIT) on cardiometabolic risk and exercise capacity in women with type 2 diabetes mellitus (T2DM). Sedentary overweight/obese T2DM women (age=44.5±1.8 years; BMI=30.5±0.6 kg/m2) were randomly assigned to a tri-weekly running-based HIT program (n=13) or non-exercise control follow-up (CON; n=10). Glycemic control, lipid and blood pressure levels, endurance performance, and anthropometry were measured before and after the follow-up (16 weeks) in both groups. Medication intake was also assessed throughout the follow-up. Improvements (P<0.05) on fasting glucose (14.3±1.4%), HbA1c (12.8±1.1%), systolic blood pressure (3.7±0.5 mmHg), HDL-cholesterol (21.1±2.8%), triglycerides (17.7±2.8%), endurance performance (9.8±1.0%), body weight (2.2±0.3%), BMI (2.1±0.3%), waist circumference (4.0±0.5%) and subcutaneous fat (18.6±1.4%) were found after HIT intervention. Patients of HIT group also showed reductions in daily dosage of antihyperglycemic and antihypertensive medication during follow-up. No changes were found in any variable of CON group. The HIT-induced improvements occurred with a weekly time commitment 56-25% lower than the minimal recommended in current guidelines. These findings suggest that low-volume HIT may be a time-efficient intervention to treat T2DM women.
Keywords: blood pressure; body composition; endurance performance; glycemic control; high-intensity interval exercise; type 2 diabetes mellitus